CACI: The Contradiction Between the Nature and Practice of Modern Manggarai Society with Its Relevance to the Character Formation of the Millennial Generation - Marselus Natar; Maria Yulita C. Age (Ridwan Institute, 2023)
Caci is one of folk game or war dances originating from Manggarai, Flores, East Nusa Tenggara. The existance and nature of Caci dance teaches the value of nasionalism, brotherhood, social interaction, rituals, resilience, courage, hospitality, tolerance and aesthetics. Nonetheless, nowadays the way milenials generation play it tend to display negative aspect compared to the internalization of Caci itself. In many cases, Caci showed more personal ego, anger, fights, grudges, hate speech (rants), and the aesthetic and entartaiment functions whis are applied in Lomes (dancing), Bokak (sound art in Nenggo and Danding), and Paci (symbolic expressions/metaphors to show the existance and quality of self) almost have no space. Caci has relevance to character formation functionality such as: the values ??of nationalism, patriotism, brotherhood, aesthetics, social interaction, rituals, toughness, courage, sacredness and manners. Caci becomes a place for the formation of people character if the act of caci is played in accordance with its essence.